Uso de sensor de vegetação para avaliação da nutrição nitrogenada na cultura do algodoeiro e sensor de solo no estudo da condutividade elétrica na cultura do milho - Tabaldi, Fabiano Maurício (2013)
The use of remote sensing techniques can eliminate the need for extensive sampling in the field, reducing the cost of sampling and increase the accuracy of the results. In this context, the present study had the following objectives: I-evaluate the effectiveness of an optical sensor for determining the nitrogen nutritional status of cotton crop subjected to different doses of N and correlate with the crop yield. II- to determine the electrical conductivity in two fields of classification Oxisols by using a sensor and relate this index with other chemical soil parameters and productivity of corn. Regarding the first objective, the experiment was conducted in the agricultural year of 2012/13 on a Oxisol with the cotton crop. The experimental design was a randomized block design with seven treatments and three replications. Treatments consisted of the following N rates: 0, 45, 90, 130, 150, 180 and 220 kg ha-1 applied at 43 days after sowing (DAS). The vegetation index readings were taken at three different times, corresponding to 63, 75 and 97 DAE with the optical sensor N-Sensor ALS ® (YARA). Concerning the objective II electrical conductivity was evaluated of two areas using the Veris ® 3100 sensor to depths of 0-30 cm and 0-90 cm. The evaluations were conducted in the agricultural year 2012/13, the cultivated culture, in both areas, was the corn. Chemical parameters of the soil and the electrical conductivity were compared by method of multiple regression 'stepwise'. Regarding the first objective, the vegetation index reading by sensor showed high correlation with N rates in three stages evaluated, this correlation was also found with the parameters plant height, dry matter and N absorbed. The highest yield of cotton was achieved with rate of 152 kg ha-1 of N. Regarding the objective II, the EC of Area 1, for 0-30 cm layer, was explained by factors V% and Mg and in the layer of 0-90 cm by SB factor. For Area II, the EC in the 0-30 cm layer, was explained by clay contente, CTCpH7,0 and SB and for 0-90 cm layer by clay content. Increasing productivity of Area 1 showed a quadratic fit with increasing EC at both depths evaluated, in Area 2 increased productivity correlated linearly with increasing EC at both depths.